Audit Quality and Earnings Management After Communicating Key Audit Matters (Kams) In the UAE – Audacity and Auditors' Perspectives - Yasser Barghathi; Simran Mirani; Naimat U. Khan (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question- Does the introduction of Key Audit Matters (KAMs) increase audit quality and reduce agency cost associated with it? Does the introduction of KAMs decrease Earnings Management (EM) and agency cost associated with it? Motivation- There have been many studies in the past few years testing the impact of KAMs on the quality of the audit and EM in the developed economies like the United States and United Kingdom, however very few studies exist in the context of the UAE. Moreover, many studies on this topic uses quantitative techniques whereas this study employs qualitative method of interview to judge the perception of auditors about the audit quality and EM in the UAE after the introduction of KAMs. Idea- The research seeks the perception of auditors about the quality of audit and EM after the introduction of communicating KAMs in the UAE. Data and Tools- A semi-structured interview is conducted with thirteen auditors –six Big-4 and seven Non-Big 4 audit firms. Findings- The findings show that the introduction of KAMs enhances the quality of audit in the form of better communication and transparency, especially, in big listed firms. It increases the managerial accountability which results in minimizing the agency cost of equity. However, the study also reveals that the auditors have the audacity to confess the pressures from clients and audit firms which lead to the hidden anomalies and EM practices that resulted in decreasing the audit quality, especially in non-Big 4 firms. Contribution- The research shows that there is no uniformity in audit practice in UAE where own nationals (Emirates) enjoy more flexibility compare to foreigners. In addition, a difference exists in the audit practices of Big-4 and Non-Big 4 auditors. The non-existence of stringent audit regulatory body lead to effect the overall quality of the audit. The government should implement a uniform and robust audit regulatory body to ensure the audit quality.
Keywords: M41; 650; Audit Quality; Earnings Management; Key Audit Matters (KAMs); United Arab Emirates (UAE); Qualitative Research; Interviews; Agency Theory